De magnetische tijd : videokunst in Nederland 1970-1985. - Bellinkx, Ruth; Boomgaard, Jeroen; Holtappels, Heiner; Kappert, Hinke; Lopez, Sebastian; Perrée, Rob; Rutten, Bart; Seijdel, Jorinde; van Driel, Anne; van Mechelen, Marga (Amsterdam Rotterdam : NAI Uitgevers Rotterdam Nederlands Instituut voor Mediakunst, MonteVideo/Time Based Arts Amsterdam, 2003)
Abramovic, Marina ; Abramovic, Marina & Ulay ; Ader, Bas Jan ; Boezem, Marinus ; Cardena, Michel ; Carrión, Ulises ; d'Armagnac, Ben ; Dedo ; Dibbets, Jan ; van Elk, Ger ; Engels, Pieter ; General Idea ; Gijzen, Wim ; De Groot, Kees ; Hoover, Nan ; Jodi ; Kaap, Gerald Van Der ; Komen, A.P. ; de Kroon, Harrie ; Livinus ; Marroquin, Raul ; van Munster, Jan ; Murphy, Karen ; Nauman, Bruce ; Paik, Nam June ; Palestine, Charlemagne ; Schippers, Wim T. ; Schouten, Lydia ; Schutter, Bert ; Servaas ; SKET ; Sluik/Kurpershoek ; Smals, Wies ; Stansfield & Hooykaas ; Tajiri, Shinkichi ; Tan, Fiona ; Theuws, Roos ; Toebosch, Moniek ; Vijselaar/Sixma ; Vos, Giny ; Vostell, Wolf
+ 1 engelstalig exemplaar
Nederlands
boek
Keywords: Nederland